Predictability of Droughts and Floods Due to El Niño and La Niña Episodes - Estoque, Mariano A.; Balmori, Rochelle Therese F. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 14 No 2 (2002))
none
Keywords: El Niño, La Niña, droughts, floods, sea surface temperature, prediction